Effect of repeated controlled ovarian stimulation on pregnancy outcomes in fresh embryo transfer cycles: a retrospective cohort study - Shiming Wang; Xiaoli Chen; Ningning Wang; Yingchun Su; Lin Qi (BMC Pregnancy and Childbirth)
Abstract Background It is ambiguous whether the multiple COS with supraphysiologic hormonal doses impact ovarian reserve functions or pregnancy outcomes. The aim is to explore the effect of multiple COS during ART on ovarian reserve function and clinical pregnancy outcomes in infertile women. Methods The retrospective study included 45,555 IVF/ICSI fresh cycles enrolled between January 2015 and March 2021 and were segregated into 5 different cycle cohorts. The participants were retrospectively grouped according to the number of repeated cycles. The primary observables symbolizing ovarian reserve function were antral follicle count (AFC) and anti-Müllerian hormone (AMH). We analyzed clinical pregnancy rate (CPR), live birth rates (LBR), and early miscarriage rate (EMR) to explore clinical pregnancy outcomes. Results Among populations with different numbers of COS cycles, regression analyses found that the number of COS cycles had no significant impact on pregnancy outcomes (p > 0.05) after adjusting for confounding factors. However, factors such as age, BMI, and embryo transfer parameters showed significant associations with pregnancy outcomes. Intra-group analysis within same population revealed that, basal FSH, basal LH, AMH, and AFC exhibit no significant distinction (P > 0.05). Cycle 2 in Group B (aOR = 8.29; 95% CI, 6.80-10.12; P = 0.000), Cycle 3 in Group C (aOR = 6.05; 95% CI, 3.28–11.15; P = 0.000) and Cycle 4 in Group D (aOR = 20.46; 95% CI, 3.05-137.24; P = 0.002) had the highest CPR within each group; Cycle 2 in Group B and Cycle 3 in Group C had the highest LBR and lowest EMR within each group, and the differences did not reached statistical significance in the remaining groups. Conclusion(s) The number of COS cycles did not significantly adversely affect pregnancy outcomes across different populations. In self-controlled comparisons within the same population, repeated COS (≤ 5 cycles) may not impair ovarian reserve function, while repeated COS (≤ 4 cycles) positively influenced clinical pregnancy outcomes, suggesting a potential cumulative effect. Graphical abstract